PH-dependent regulation of SQSTM1/p62 during autophagy. Issue 1 (2nd January 2019) - Kwon, Do Hoon; Kim, Leehyeon; Song, Hyun Kyu
ABSTRACT: During macroautophagy/autophagy, SQSTM1/p62 plays dual roles as a key mediator of cargo selection and as an autophagic substrate. SQSTM1 links N-degrons and/or ubiquitinated cargoes to the autophagosome by forming homo- or hetero-oligomers, although its N-degron recognition and oligomerization mechanisms are not well characterized. We recently found that SQSTM1 is a novel type of N-recognin whose ZZ domain provides a negatively-charged binding pocket for Arg-charged N-degron (Nt-Arg), a prototype type-1 substrate. Although differences in binding affinity exist for each N-degron, SQSTM1 also interacts with type-2 N-degrons, such as Nt-Tyr and Nt-Trp. Intriguingly, interactions between SQSTM1's ZZ domain and various N-degrons are greatly influenced by pH-dependent SQSTM1 oligomerization via its PB1 domain. Because cellular pH conditions vary from neutral to acidic depending on the stage of autophagy, the pH-dependent regulation of SQSTM1's oligomerization must be tightly coupled with the autophagic process.